DETERMINANTS OF ACCOUNTING CONSERVATISM IN BASIC MATERIALS COMPANIES - Triponia, Fransiska, Tanto (Jurnal Akuntansi Kontemporer, 2026)
Research Purposes: This study analyzes the effect of Debt Covenant, Board of Commissioners, and Profitability on Accounting Conservatism in Indonesia's Basic Materials sector (2020-2024). Research Methods: Using purposive sampling, 43 companies from a population of 113 were selected based on pre-2020 IPO status, medium market capitalization, and consistent audited financial reporting. A quantitative approach using secondary data was employed and analyzed in SPSS version 26. Research Results and Findings: Debt Covenant demonstrates a negative effect on conservatism, whereas Board of Commissioners and Profitability show positive influences. These findings reveal the contextual nature of governance-performance relationships in accounting conservatism, highlighting how industry-specific characteristics and business environment significantly shape their effectiveness.